ANALISIS VIDEO PEMBELAJARAN ANIMASI SEBAGAI MEDIA DALAM KETERAMPILAN MENULIS TEKS EKSPLANASI - Owa, Yuliana Silvia; Dian Indihadi; Muhammad Rijal Wahid Muharram (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning Indonesian at the elementary school level often faces challenges in increasing student interest and understanding. A higher level of thinking and creativity is required, particularly with regard to writing skills. Writing is one of the highest levels of learning in Indonesian because students create something from their thoughts and knowledge, particularly when writing explanatory texts. Since the implementation of the 2013 curriculum, explanatory texts have been taught in elementary school, so it is not uncommon for students to have difficulty writing them. Therefore, a contextualized, integrated approach is needed. As technology advances, digital media can be an innovative solution to increase student engagement and understanding of explanatory writing. This study aims to educate on using animated instructional videos as a digital medium. This study uses a qualitative descriptive research method. The data collection technique is a literature review. The research stages are based on both primary (field observations) and secondary (existing) data. The results of the literature review on using animated video lessons as a digital medium are promising for improving writing skills among elementary school students.